THE USE OF GENRE BASED APPROACH ON STUDENTS’ WRITING RECOUNT ACHIEVEMENT - Mufida Fatmawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
Writing is one of language skills that students learn in the class, and based on the pre-research observation, students still have difficulty in determining the correct grammar to write. An appropriate approach can be applied in the class to help students to overcome their difficulty in determining the grammar. This research was conducted to prove the effect of Genre Based Approach on students’ writing recount text. This research uses pre-experimental method and one group pretest-posttest design. The sample was chosen by random sampling technique. The sample in this research is the second-grade students of Cibungbulang Junior High School. To collect the data, the researcher uses pre-test and post-test of their writing recount product. After collecting the scores of pretest and posttest, then they were analyzed using t-test. The result of the analysis shows that the null hypothesis is rejected (H0) whereas alternative hypothesis is accepted (Ha). It means, the use of Genre Based Approach significantly affect and effective to train students in writing.